Desempenho produtivo e verminose gastrointestinal de ovelhas e cordeiros suplementados em pastagem - Thais Fernanda Farias de Souza Arco (2023)
The hypotheses were tested that the greater nutritional contribution, in structural conditions of lowered pastures, improves the productive performance and reduces the gastrointestinal verminosis of lactating ewes and suckling lambs. In the first article, the effect of supplying 0.5 and 1.0% BW of energy protein supplementation was evaluated for ewes kept on lowered and non-lowered Marandu grass. There was no interaction or effect of the isolated factors on the productive performance and gastrointestinal verminosis of the ewes. Gastrointestinal verminosis was affected by the evaluation period, with a higher parasite level at birth, with a reduction throughout the lactation period. Worm rates were affected by the interaction between nutritional levels and pasture management. A higher rate was observed in ewes supplemented with 1.0% BW on lowered pastures at 30 days postpartum, while at 90 days, the highest rate was in the group supplemented with 0.5% BW on non-lowered pastures. Estimates of forage intake were similar among ewes. Ewes supplemented with 1.0% BW showed higher BCS at 60 days postpartum. The levels of neutral detergent fiber (NDF) and acid detergent fiber (ADF) were affected by the months of evaluation, with higher levels during the dry season. The second article evaluated the effects of pasture structure and maternal supplementation on the productive performance, body condition score and gastrointestinal verminosis of 50 Texel lambs. Maternal supplementation affected the weight and BCS of lambs at 60 days. Lambs with a maternal nutritional level of 1.0% BW showed higher pasture consumption from 30 to 60 days, which may be associated with the higher result of eggs per gram of feces (FEC) observed in this group at 90 days. The levels of neutral detergent fiber (NDF) and acid detergent fiber (ADF) of the leaves were higher in the lowered pastures. Pasture morphological composition was influenced by pasture management and supplement intake. The leaf/stem ratio of the pasture was below the critical value throughout the experimental period. The high FEC of the lambs at 60 and 90 days did not affect their supplement intake and productive performance, being attributed the resilience of the lambs against parasitism. The average supply of 300 g/day of supplement in a creep feeding system to the lambs may have contributed to the acquisition of resilience.